Diversity and diversification in banana: How in silico chromosome painting opens new perspectives for the conservation of an iconic fruit - Sardos, Julie (2025)
With the rise of genomics, the characterization of crop genetic resources has entered a new era. Here, we present how the SNP-based characterization of ancestry along chromosomes – the in silico chromosome painting approach - is game changing for the conservation and the use of banana genetic resources. Banana is a vegetatively propagated crop presumably composed of clonal cultivars and clonal cultivar groups. Using in silico chromosome painting enables to provide fine-scale genomic identity to cultivars and cultivar groups. Doing so, it allows the identification of fixed clonal diversification events such as mitotic recombination and indels, sometimes providing a unique genomic signature to specific varieties. It also allowed to identify pluri-clonal cultivars groups in which the different varieties result from different sexual events. By enabling the characterization of a hidden component of banana diversity, this method can be used for the routine management of ex-situ collections, notably for gap analysis and for the regular check of the genetic integrity of the germplasm. These findings also constitutes a first path towards a wider and wiser use of banana genetic resources in breeding, notably through the selection of targeted ancestral genomic regions in breeding lines parents. Finally, these discoveries could also trigger the direct use of existing banana genetic resources to buffer the effects of climate change on traditional agrosystems.